Deficiency Anemia in Children. Etiopathogenesis, Clinical Course of Hemopoietic Factor Deficiency According to Severity Levels - oʻgʻli, Fozilov Miralisher Mirkamol; oʻgʻli, Mamatqulov Ismoil Gʻaybullo; o’g’li, Anvarov Navro’zbek Anvar; o‘gli, Akramov Abdullo Ahmad (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article Deficiency anemia in children and Etiopathogenesis, clinical course of hemopoietic factor deficiency according to severity levels is described in detail.